دورالإعلام في تطوير البحث في الإقتصاد الإسلامي - Ø¹Ø¨Ø¯ Ø§Ù„ØØ§ÙØ¸ Ø§Ù„ØµØ§ÙˆÙŠ (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2009)
This paper addressed the role of media in the development of research in Islamic Economics, taking off through the fact that both flags from the social sciences and the impact each other and are influenced by informed historical juncture in which we live globalization paper focuses on the concept of positive information which is based on the theory of social responsibility with an analytical reading of the theories other information and the extent to which the area of research with reference to the reality of Islamic Economics, development, and focus on experienced in research, in particular, the paper also came to the nature of the relationship between the media and Islamic economy through the reality of Islamic Economics in the media and concludes the paper to know the aspects of Algosorvi both sides and put the requirements of must be entered into the real world so that there is a positive relationship is achieved in which a role for media in the development of research in Islamic Economics.